Potassium application enhances drought tolerance in sesame by mitigating oxidative damage and regulating osmotic adjustment - Fang, Sheng; Yang, Huiyi; Wei, Guangwei; Shen, Tinghai; Wan, Zehua; Wang, Min; Wang, Xiaohui; Wu, Ziming (Frontiers in Plant Science, 2022)
Potassium (K) is known for alleviating the negative effects of abiotic stresses on plants. To explore the functions of K in controlling reactive oxygen species (ROS), antioxidants activities, and osmoregulation in sesame under drought stress, a pot experiment was conducted with three K levels (0, 60, 120 kg ha–1, recorded as K0, K1, K2, respectively) and exposed to well-watered (WW, 75 ± 5% soil relative water content) and drought-stressed (DS, 50 ± 5% soil relative water content) conditions. The results showed that DS stimulated the production of ROS such as increased hydrogen peroxide (H2O2), leading to lipid peroxidation as characterized by higher malondialdehyde (MDA), and consequently resulting in the decline in relative water content (RWC) and photosynthetic pigments as compared to WW plants. These adverse effects have been exacerbated as drought stress prolonged. Concurrently, K application alleviated the magnitude of decline in the RWC, chlorophyll a and chlorophyll b, and plants applied with K exhibited the superior growth, with the optimal mitigation observed under K2 treatment. Additionally, DS plants treated with K exhibited lower lipid peroxidation, higher antioxidant activities, and increased osmotic solutes accumulation in comparison with plants under K deficiency, which suggested exogenous K application mitigated the oxidative damages and this was more prominent under K2 treatment. Noteworthily, the proline and soluble protein respectively dominated in osmotic regulation at 3 d and 6 d of drought stress according to the analysis of quantitative comparison among different osmotically solutes. Based on the correlation of aforementioned traits and analysis of variation on interaction effects of drought stress and potassium, we propose that superoxide dismutase (SOD), glutathione reductase (GR), and MDA could be critical indicators in balancing ROS detoxification and reproduction. In summary, our studies suggest that optimized K application keeps a balance between the production of antioxidants and ROS, and simultaneously affects osmoregulation to alleviate the damage from drought stress.